Insular species swarm goes underground: two new troglobiont Cylindroiulus millipedes from Madeira (Diplopoda: Julidae) - Reboleira, Ana Sofia P. S.
Two new species of the genus Cylindroiulus Verhoeff, 1894, C. julesvernei and C. oromii, are described from the subterranean ecosystem of Madeira Island, Portugal. Species are illustrated with photographs and diagrammatic drawings. The new species belong to the Cylindroiulus madeirae-group, an insular species swarm distributed in the archipelagos of Madeira and the Canary Islands. We discuss the differences between the new species and their relatives and present information on the subterranean environment of Madeira. An updated overview of the subterranean biodiversity of millipedes in Macaronesia is also provided.